Development of a Simulator to Mimic VMware vCloud Director (VCD) API Calls for Cloud Orchestration Testing - Sayyed, Zahir (International Journal of Computational and Experimental Science and Engineering, 2025)
Orchestration systems, particularly those on VMware vCloud Director (VCD), play a vital role in managing multi-tenant virtualized environments. Nonetheless, it is problematic to test automation scripts and orchestration workflows directly on production or staging VCD infrastructure: it is expensive, inaccessible, and may endanger live services. This paper provides an overview of the design and implementation of an API call simulator tailored to a specific domain, aiming to create safe, efficient, and repeatable testing environments for developers and DevOps engineers. In contrast to generic mocking tools, this simulator offers a feature set tailored to VCD-specific requirements, including stateful API behavior, vApp mock lifecycles, and dynamic responses. It confirms popular HTTP requests on core end-points such as sessions, vApps, catalogs, and networks, offering a precise test proxy that does not map virtualization to the backend. The simulator also fits well in CI/CD environments and facilitates chaos testing through fault injection. A detailed analysis demonstrates its high fidelity to real VCD behavior, with low latency under concurrent load, and developers were satisfied with the results. Applications include use as a development sandbox tool, a disaster recovery testing tool, an educational tool, and a certification tool. The paper concludes by suggesting the adoption of these approaches on a broader scale, both in enterprise settings and those involving cloud training. The scalability of the simulator ultimately addresses the continuity limitations of present-day testing in cloud orchestration.